Beyond the farm: stakeholder perspectives on precision livestock farming in the swine industry - Akinyemi, Babatope E.; Jessiman, Lesley; Turner, Simon P.; Siegford, Janice M. (Frontiers in Animal Science, 2025)
IntroductionThis study explores the Precision Livestock Farming (PLF) technology perceptions and data needs of off-farm swine industry stakeholders. The aim was to increase our understanding of PLF’s real-world applicability beyond farm operations. MethodsUsing focus group discussions, five professionals—spanning government official, animal scientists, food processors, and retail representatives—offered insights on ideal data types and practical concerns associated with PLF adoption. Using the Nominal Group Technique (NGT), we determined that participants have unique data needs, with no clear consensus on data priorities for PLF. We conducted a second focus group following normal focus group protocols, allowing us to further explore participants’ PLF priorities, nuanced perspectives, and shared beliefs. Results and discussionWe identified five themes: “To Split the Check or Not to Split the Check; Knowing the Benefits is Key; Reconciling Profit and Welfare in PLF; What Use is PLF to the Animal Anyway? and The Value and Caveats of PLF Data. The benefits of PLF data to participants were closely tied to clear cost-sharing structures, meaningful benefits for diverse stakeholders, and assurances about data control. Stakeholders voiced concerns around financial feasibility, ethical implications, and practical barriers in terms of data management. Overall, addressing these complex but interrelated needs and concerns by other stakeholders can make data generated by PLF useful beyond the farm and provide additional incentives to advance PLF adoption in the swine industry. This finding may provide actionable insights to inform strategies that support both the technological advancement and ethical sustainability of PLF in animal agriculture.